Third AsiaBlight Meeting. Beijing, China, 25-27 October 2019 - Lasserre, C.; Maurer, A.; Li, M.; Kear, P.; Lu, X.; Andrade-Piedra, J.L. (International Potato Center, 2020)
The 3rd. AsiaBlight meeting was hosted by CCCAP and the College of Plant Protection at the China Agricultural University (CAU) in Beijing in October 2019. The meeting included sessions on the following topics: (1) potato late blight in Asia and beyond; (2) late blight biology, genetics, and population dynamics in Asia; (3) plantpathogen interactions and potato resistance; and (4) late blight management, fungicides, and decision support systems. The program included 33 oral presentations (7 of them presented as posters as well), and three posters (Annex 1). The meeting was attended by 111 participants (Annex 2) from 17 countries: Bangladesh, Belgium, Chile, China, Georgia, India, Japan, Nepal, the Netherlands, Pakistan, Peru, the Philippines, the Republic of Korea, the United Kingdom, the United States, Uzbekistan, and Vietnam.